Moralne standardy przedstawicieli kierownictwa ds. systemów zarządzania jakością - Rogala, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The report undertakes the subject of relation between management quality and business ethics. An analysis of the content of ISO 9000 series was carried out with focus on rules of ethical conduct and requirements of social responsibility concept. The research, carried out in five chosen organizations, identified the most common ethical problem situations encountered by management representatives for quality management systems. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 128-133